A PCPDTTPD-based narrow bandgap conjugated polyelectrolyte for organic solar cells. (14th February 2018) - Brebels, Jeroen; Kesters, Jurgen; Defour, Maxime; Pirotte, Geert; Van Mele, Bruno; Manca, Jean; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Abstract: Extensive research on organic photovoltaics has granted impressive power conversion efficiencies, nowadays exceeding 13% for state-of-the-art photoactive material combinations. Nevertheless, different strategies can be adopted to further enhance the efficiency and the competitiveness with alternative photovoltaic technologies. Conjugated polyelectrolytes have been applied as anode or cathode interlayers to optimize ohmic contacts and lower the contact resistance, thereby improving the ultimate device efficiency. Here, we present an interlayer material belonging to the emerging class of narrow bandgap conjugated polyelectrolytes, based on an imidazolium functionalized 4 H -cyclopenta[2, 1- b :3, 4- b ']dithiophene (CPDT) as the electron-rich polymer building block and 4 H -thieno[3, 4- c ]pyrrole-4, 6(5 H )-dione (TPD) as the electron-deficient subunit. The ionic polymer is applied as cathode interlayer for PBDTTPD:[70]PCBM (poly[bis(2′-ethylhexyloxy)benzo[1, 2- b :4, 5- b ′]dithiophene- alt - N -octylthieno[3, 4- c ]pyrrole-4, 6-dione]:[6, 6]-phenyl-C71 -butyric acid methyl ester) bulk heterojunction polymer solar cells, improving the overall device performance from 6.9 to 7.8%. Graphical abstract: Image 1 Highlights: An ionic narrow bandgap conjugated polyelectrolyte is prepared. The material is used as a cathodic interlayer in organic solar cells. A uniform coverage of the photoactive layer is achieved. A 13% increase in power conversion efficiency is obtained.